Social and financial incentives for overcoming a collective action problem - Bakhtiar, M. Mehrab; Guiteras, Raymond; Levinsohn, James; Mobarak, Ahmed Mushfiq (Yale University, 2021)
Addressing public health externalities often requires community-level collective action. Each person’s sanitation behavior can affect the health of neighbors. We report on a cluster randomized controlled trial conducted with 19,000 households in rural Bangladesh where we randomized (1) either group financial incentives or a non-financial “social recognition” reward, and (2) asking each household to make either a private pledge or a public pledge to maintain hygienic latrines. The group financial reward has the strongest impact in the short term (3 months), inducing a 7.5-12.5 percentage point increase in hygienic latrine ownership. Getting people to publicly commit to maintaining and using a hygienic latrine in front of their neighbors induced a 4.2-6.1 percentage point increase in hygienic latrine ownership in the short term. In the medium term (15 months), the effect of the financial reward dissipates while the effect of the public commitment persists. Neither social recognition nor private commitments produce effects statistically distinguishable from zero.